Semeando práticas: a rede que performa a prática ecológica - Becker, Rúbia Goi (2024)
Among the alternative spaces emerging in the everyday life of the city, those supported by assumptions that confront the status quo of the globalized way of life stand out, revealing new ways of living and existing, strange to the industrial logic of producing, distributing, and commercializing, related to the business world. Within this scope, organizing forms that seem to lose their meaning within the market logic, such as initiatives linked to ecology, represent a survival alternative for groups that find themselves on the margins of the standards of living and consumption followed by capitalist society. Such initiatives stand as a way to recognize and reclaim organizing forms that are sometimes rendered invisible by the modern and Western construction of thought. By conceiving ecology as a social practice, this thesis relies on Actor-Network Theory (ANT) and After as a theoretical-methodological assumption, focusing on the organizing processes that produce local orderings and collectively shape social reality. The thesis argues that "ecological practice, while producing, reproducing, and transforming reality, weaves a network of movements, associations, doings, and knowings enacted by a process of becoming." Building on this understanding, the objective is to understand how ecological practice is constructed, maintained, and transformed through associations among heterogeneous actors in a network. To understand ecology as practice, it is necessary to reveal the extensive sociotechnical network, a point where Actor-Network Theory (ANT) and After as a theoretical-methodological perspective, under a political and performative bias, presuppose that data are obtained in the interaction between subject and object, both constituted and reconstituted during the course of the research process. In this sense, Actor-Network Theory and After is used to conduct the research journey. The hinterlands (LAW, 2004) are adopted as an analysis technique that makes it possible to highlight the complex of relationships that make visible part of the network flow that performs ecological practice. The findings indicate that ecological practice is performed by the agroecological network, produced in the relations among farmers, cooperatives, ecological fairs, NGOs, and social movements in association with heterogeneous actors. Ecological practice as a becoming function as an ideology, a lifestyle, a consuming and producing, and in the political relationship between society and nature. While the agroecological network as a doing enables the conditions for the practice to be produced, reproduced, and transformed in the associations and ruptures that enact the actors and practices, allowing for a continuous restoration of the forged relationships between them. Ecology as a becoming and agroecology as a doing are connected and intertwined by relationships that determine and condition one another, each existing through the other. The agroecological network represents the journey on the edge, the explored path that cannot be measured by traditional standards because it is in the very process of performing ecological practice that actors in relation associate and disassociate themselves. The findings represent a preliminary step towards addressing broader social and economic questions, with a view to encouraging local initiatives for the production, commercialization, and relationship with healthy food.